More than just paw-blicity the online communicative goals, plans, and actions of animal rescuers - Bautista, Jose Lorenzo D.
This study explores the online communication strategies employed by animal rescuers to promote animal welfare. In particular. the study investigates how animal rescuers construct their online messages. considering their goals, image construction, and platform usage. Drawing on Dillard's (2008) Goals, Plans, Action theory. Goffman's (1956) concept of Impression Management, and Gibson's (1979) A ffordances theory, semi-structured interviews were conducted with prominent animal rescuers. The findings reveal a convergence of goals among rescuers, centered around gaining assistance, sharing activities, changing orientations, improving relationships, promoting compassion, and encouraging adoption. Animal rescuers depend on online communities for support and utilize targeted donation appeals. emphasizing transparency and accountability for building trust and maintaining audience connections. Emotional appeals, storytelling, and relatability are used to inspire others to join their mission. The study reveals challenges faced by animal rescuers, such as financial constraints and social media limitations, while emphasizing the empowering role of social media platforms in enabling meaningful impact on animal welfare. These rescuers engage their communities and amplify their advocacy through strategic and humble communication. By exploring the dynamics of digital communication in animal welfare, this study provides valuable insights and effective strategies for engaging online communities and advancing the cause of stray animals.